PERANCANGAN FASILITAS PARKIR PASAR BLAURAN SURABAYA - Ahmad Resahidayat; Intan Kusumaningayu; Farida Murti (PS S1 Arsitektur. Jurusan Arsitektur, Fakultas Teknik Universitas Sam Ratulangi Manado, 2024)
This study discusses the design of parking facilities at Pasar Blauran Surabaya in response to the problem of limited parking space that affects the smooth operation of the market and the convenience of visitors. Through a mixed qualitative and quantitative approach, this research conducts an in-depth analysis of the parking conditions at the market. Primary data were collected through field surveys, including observations of parking patterns and interviews with market traders and visitors. The results show that parking space at Pasar Blauran is still limited, leading visitors and traders to often choose unofficial parking spots, increasing the risk of congestion and traffic problems. The limitation of parking space at Pasar Blauran Surabaya is a serious issue that affects the market's operation and the comfort of visitors and traders. This research identifies the factors causing and the impacts of this issue and offers solutions. Through a mixed qualitative and quantitative approach, including literature reviews, field surveys, and data analysis, the main findings and recommendations are presented. The research site is Pasar Blauran, located in a densely populated area in South Surabaya. The results are expected to provide guidance for local governments, market managers, traders, and the community in improving the quality and sustainability of the market. Keywords: Pasar Blauran, Surabaya, parking facilities, limited parking space, parking conditions.